The Role of Promotion and Transfer Policy in Improving Staff Performance: A Case Study at the University of Dongola, Republic of Sudan - Ezieldin, Modthir; Al-Moumein, Ameer (The Arab Journal of Administration, 2019)
The study aimed to identify the role of a specific policy for promotion and transfer in raising the efficiency of the performance of the employees in the University of Dongola, Republic of Sudan. The problem of this study was the failure to adhere to a specific promotion and transfer policy at University. After completing the theoretical aspect, a questionnaire was distributed to a stratified sample of faculty and staff members. The sample was selected in the random stratified sample, and a simple sample was selected from each stratum. It confirmed that there is a statistically significant relationship between the dependent variable (employee performance efficiency), the independent variables (The existence of a specific promotion policy and the existence of a specific transfer policy), has the value of (t) calculated for the regression coefficient (17.13) and the level of significance (0.001). It was found that there is a linear correlation between independent and dependent variables, the correlation coefficient (0.79), the regression coefficient (1.10), and the effect of independent variables on the dependent variable were 62%. It recommended that the university should establish a specific policy for the promotion and transfer of employees, addressing the negative effects and grievances resulting from the application of this policy and linking the promotion and transfer policies with career planning.